Innovations and challenges in grammar - McCarthy, Michael 1947- (Routledge, 2021)
Part I. Where we came from: 1. Introduction -- 2. Grammar: Where did it all come from? -- 3. Eras of change and innovation: The eighteenth and nineteenth century -- Part II. Innovations and Challenges: 4. Grammar and the public, grammar for ELT -- 5. Innovation: Major new grammatical theories -- 6. Grammar as data: corpus linguistics -- 7. Grammar and discourse -- 8. Grammar, language teaching and language learning -- 9. Grammar at large
Includes bibliographical references and index
Keywords: Kontrastive Grammatik; Grammar, Comparative and general; Language and languages / Grammars; Language and languages / Philosophy